2018
DOI: 10.1007/s11356-018-1702-2
|View full text |Cite
|
Sign up to set email alerts
|

Oral exposure of deltamethrin and/or lipopolysaccharide (LPS) induced activation of the pulmonary immune system in Swiss albino mice

Abstract: The deltamethrin, a synthetic pyrethroid, is used worldwide and has been linked with several type of acute toxicity. However, effect of low level of deltamethrin alone or in combination with the microbial antigen on pulmonary system is not understood. Lipopolysaccharide (LPS) was used as antigen which is a key inflammatory component of gram-negative bacteria, which induces a distinctive pattern of cytokine release that regulates inflammation. The aim was to determine whether chronic exposure to a low level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…In our study, mice were injected with LPS or DOX to investigate if the observed decline in sSelectin-L is specific to radiation. Within one day of LPS or DOX injection, lymphocyte counts significantly decreased compared to the control group, consistent with previous reports [ 30 ]. However, there was no significant difference in serum sSelectin-L before and after LPS or DOX injection, indicating that the alteration in sSelectin-L was more specific and accurate in response to radiation injury and not affected by bacillosis or drug-induced DNA damage.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, mice were injected with LPS or DOX to investigate if the observed decline in sSelectin-L is specific to radiation. Within one day of LPS or DOX injection, lymphocyte counts significantly decreased compared to the control group, consistent with previous reports [ 30 ]. However, there was no significant difference in serum sSelectin-L before and after LPS or DOX injection, indicating that the alteration in sSelectin-L was more specific and accurate in response to radiation injury and not affected by bacillosis or drug-induced DNA damage.…”
Section: Discussionsupporting
confidence: 92%
“…The distinct weight loss, with significant leukocyte decrease and neutrophil decrease after LPS injection suggesting the bacillosis model was constructed successfully ( Supplemental Figs. 6a–c ) [ 29 , 30 ]. The lymphocyte count decreased sharply on the first day after injection, and then began to recover, but it remained significantly lower than the control group until the 7th day (P < 0.05) ( Fig.…”
Section: Resultsmentioning
confidence: 99%